Constructing Deal Networks: Brokers as Network “Architects” in the U.S. IPO Market and Other Examples - Pollock, Timothy G.; Porac, Joseph F.; Wade, James B. (Academy of Management Review, 2004)
We introduce the concept of the network architect to extend theory explaining how brokers create and manage structural holes in mediated markets. We argue that a broker's social resources and dependence on the market, along with exogenous deal conditions, influence the broker's motivations and willingness to make tradeoffs between long-term and short-term considerations when constructing deal networks. We develop our model and propositions in the context of the U.S. initial public offerings market and then generalize these arguments to other market contexts.